A facile and low-cost length sorting of single-wall carbon nanotubes by precipitation and applications for thin-film transistors. Issue 6 (22nd January 2016) - Gui, Hui; Chen, Haitian; Khripin, Constantine Y.; Liu, Bilu; Fagan, Jeffrey A.; Zhou, Chongwu; Zheng, Ming
Abstract : We report for the first time a general phenomenon of length-dependent precipitation of surfactant-dispersed carbon nanotubes by polymers, salts, and their combinations. Abstract : Semiconducting single-wall carbon nanotubes (SWCNTs) with long lengths are highly desirable for many applications such as thin-film transistors and circuits. Previously reported length sorting techniques usually require sophisticated instrumentation and are hard to scale up. In this paper, we report for the first time a general phenomenon of a length-dependent precipitation of surfactant-dispersed carbon nanotubes by polymers, salts, and their combinations. Polyelectrolytes such as polymethacrylate (PMAA) and polystyrene sulfonate (PSS) are found to be especially effective on cholate and deoxycholate dispersed SWCNTs. By adding PMAA to these nanotube dispersions in a stepwise fashion, we have achieved nanotube precipitation in a length-dependent order: first nanotubes with an average length of 650 nm, and then successively of 450 nm, 350 nm, and 250 nm. A similar effect of nanotube length sorting has also been observed for PSS. To demonstrate the utility of the length fractionation, the 650 nm-long nanotube fraction was subjected to an aqueous two-phase separation to obtain semiconducting enriched nanotubes. Thin-film transistors fabricated with the resulting semiconducting SWCNTs showed a carrier mobility up to 18 cm 2 (V s) −1 and an on/off ratio up to 10 7 . Our result sheds new light on the phase behavior of aqueous nanotube dispersions under high concentrations of polymers and salts, and offers a facile, low-cost, and scalable method to produce length sorted semiconducting nanotubes for macroelectronics applications.